2020
DOI: 10.18608/jla.2020.71.5
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Collaboration as a Process with Theory-driven Learning Analytics

Abstract: Although collaboration is considered a key 21st-century skill, oftentimes it is only assessed through the outcome measures of individual learners. In this paper, we draw upon collaborative cognitive load theory (CCLT) to explain the process of collaboration in learning from the point of view of the collective, rather than an individual learner. Using CCLT we suggest a new method of measuring the process of collaboration regardless of its outcome measures. Our approach — Collaborative Learning as a Process (CLa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 53 publications
1
20
0
1
Order By: Relevance
“…CSCL is a complex knowledge construction process based on social interaction (Saqr et al., 2020). However, most studies in the area have focused exclusively on learning outcomes rather than considering collaborative learning processes (Kent & Cukurova, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…CSCL is a complex knowledge construction process based on social interaction (Saqr et al., 2020). However, most studies in the area have focused exclusively on learning outcomes rather than considering collaborative learning processes (Kent & Cukurova, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have demonstrated the potential of LA for transforming education, there has been little attention paid to the design and implementation of IS with LA capabilities [26]. As a result, the study attempts to propose essential guidelines and a unified framework in hope of that educational IS researchers can unite the forces with the learning scientists and other research communities to push the LA agenda forward This conceptual study responds to the recent calls to perform theory-based LA research [10,19] and to support the application of learning analytics in higher education [18,24]. The framework proposed in this paper is easy to follow to design a theory-based learning analytics information system.…”
Section: Discussionmentioning
confidence: 98%
“…Hence, the instructors participating in our study might have been concerned about their students' socio‐emotional state and collaboration and thus showed more interested in such data, and intention to make informed decisions based on data related to social and emotional aspects of online learning. Notably, information about collaboration and emotions could be detected from students' interactions with the online learning environment; hence, this may serve instructors in their decision‐making process (Baker et al., 2012; Calvo & D’Mello, 2010; Herder et al., 2018; Kent & Cukurova, 2020).…”
Section: Discussionmentioning
confidence: 99%